Microbial extraction of chitin from seafood waste using sugars derived from fruit waste-stream - Tan, Yun Nian (2021)
Chitin and chitosan are natural amino polysaccharides that have exceptional biocompatibility in a wide range of applications such as drug delivery carriers, antibacterial agents and food stabilizers. However, conventional chemical extraction methods of chitin from marine waste are costly and hazardous to the environment. Here we report a study where shrimp waste was co-fermented with Lactobacillus plantarum subsp. plantarum ATCC 14917 and Bacillus subtilis subsp. subtilis ATCC 6051 and chitin was successfully extracted after deproteinization and demineralization of the prawn shells. The glucose supplementation for fermentation was replaced by waste substrates to reduce cost and maximize waste utilization. A total of 10 carbon sources were explored, namely sugarcane molasses, light corn syrup, red grape pomace, white grape pomace, apple peel, pineapple peel and core, potato peel, mango peel, banana peel and sweet potato peel. The extracted chitin was chemically characterized by Fourier Transform Infrared Spectroscopy (FTIR) to measure the degree of acetylation, elemental analysis (EA) to measure the carbon/nitrogen ratio and X-ray diffraction (XRD) to measure the degree of crystallinity. A comparison of the quality of the crude extracted chitin was made between the different waste substrates used for fermentation and the experimental results showed that the waste substrates generally make a suitable replacement for glucose in the fermentation process. Red grape pomace resulted in recovery of chitin with a degree of deacetylation of 72.90%, a carbon/nitrogen ratio of 6.85 and a degree of crystallinity of 95.54%. These achieved values were found to be comparable with and even surpassed commercial chitin.